2006
DOI: 10.2109/jcersj.114.963
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth of Micron-Sized Grains in Undoped and Cobalt Oxide Doped Ceria Solid Solutions

Abstract: Isothermal grain growth experiments have been conducted for undoped as well as cobalt oxide doped CeO 2 and Ce 0.8 Gd 0.2 O 1.9 CGO20 . Due to the solute drag effect of the dissolved gadolinium ions, the grain boundary mobility of CGO20 was significantly lower than that one of CeO 2 . The addition of cobalt oxide increases the grain boundary mobility of CGO20. This increase is assigned to the formation of a characteristic cobalt oxide rich grain boundary film. In undoped and cobalt oxide doped CGO20, a transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…3b, the grain sizes did not markedly increase during a heating time of t ¼ 1/60 to 50 h around T ¼ 1173 K in the heating experiment without syngas production. These experimental results observed with XRD are available in the estimation of sintering extent in a late period with heating time from $2 to $100 h. [27][28][29]35 The familiar grain growth equation in the late period is expressed by:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b, the grain sizes did not markedly increase during a heating time of t ¼ 1/60 to 50 h around T ¼ 1173 K in the heating experiment without syngas production. These experimental results observed with XRD are available in the estimation of sintering extent in a late period with heating time from $2 to $100 h. [27][28][29]35 The familiar grain growth equation in the late period is expressed by:…”
Section: Resultsmentioning
confidence: 99%
“…Sintering mechanism of pure and doped ceria under high temperatures without syngas production has been reported in the literatures. [22][23][24][25][26][27][28][29][30][31][32][33] In this study, we experimentally investigate the effect of specic surface area on syngas production of pure ceria powders during heating without syngas production (further referred to as heating experiments) and during an isothermal MPO-CDS thermochemical redox cycling (further referred to as cycling experiments). The temperatures are varied in the range 973-1773 K in the heating experiments, whereas the reduction and oxidation temperatures are xed at 1173 K in the cycling experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent sintering and grain growth studies of cobalt oxide doped CGO20 suggested that cobalt oxide doping acts as an activator material [20,21]. Activated sintering has extensively been described for the case of Bi 2 O 3 -doped ZnO and manifests itself mainly in increased shrinkage rates below the eutectic temperature combined with intergranular films [22].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, amorphous metal oxide thin fi lms have been reported to exhibit similar crystallization kinetic rules and characteristics as glass-based systems, [ 13 ] for instance, Kissinger crystallization activation energies between 1-3 eV, [ 14 ] JohnsonMehl-Avrami characteristics, [ 15 , 16 ] and crystallization enthalpies around 90-100 J g −1 .…”
Section: Introductionmentioning
confidence: 99%